Antitumoral Activity of Snake Venom Proteins: New Trends in Cancer Therapy. (13th February 2014) - Calderon, Leonardo A.; Sobrinho, Juliana C.; Zaqueo, Kayena D.; de Moura, Andrea A.; Grabner, Amy N.; Mazzi, Maurício V.; Marcussi, Silvana; Nomizo, Auro; Fernandes, Carla F. C.; Zuliani, Juliana P.; Carvalho, Bruna M. A.; da Silva, Saulo L.; et al.
Abstract : For more than half a century, cytotoxic agents have been investigated as a possible treatment for cancer. Research on animal venoms has revealed their high toxicity on tissues and cell cultures, both normal and tumoral. Snake venoms show the highest cytotoxic potential, since ophidian accidents cause a large amount of tissue damage, suggesting a promising utilization of these venoms or their components as antitumoral agents. Over the last few years, we have studied the effects of snake venoms and their isolated enzymes on tumor cell cultures. Some in vivo assays showed antineoplastic activity against induced tumors in mice. In human beings, both the crude venom and isolated enzymes revealed antitumor activities in preliminary assays, with measurable clinical responses in the advanced treatment phase. These enzymes include metalloproteases (MP), disintegrins, L-amino acid oxidases (LAAOs), C-type lectins, and phospholipases A2 (PLA2 s). Their mechanisms of action include direct toxic action (PLA2 s), free radical generation (LAAOs), apoptosis induction (PLA2 s, MP, and LAAOs), and antiangiogenesis (disintegrins and lectins). Higher cytotoxic and cytostatic activities upon tumor cells than normal cells suggest the possibility for clinical applications. Further studies should be conducted to ensure the efficacy and safety of different snake venom compounds for cancer drug development.